Respuesta :

The solution is 22.5

To solve the given equation, rewriting the equation -

√(2x + 3) - 7 = 0

Shifting 7 to the Right Hand Side of the equation

√(2x + 3) = 7

Taking square on both sides of the equation

(√(2x + 3))² = 7²

Solving the square

2x + 3 = 49

Shifting 3 to the Right Hand Side of the equation

2x = 49 - 3

Performing subtraction on Right Hand Side of the equation

2x = 45

Shifting 2 to the Right Hand Side of the equation

x = 45 ÷ 2

Performing division on the Right Hand Side of the equation

x = 22.5

Hence, the solution is 22.5

Learn more about calculations on solving the expression -

https://brainly.com/question/19406107

#SPJ4